An EFL Experience in Undergraduate Thesis Writing: An Auto-Ethnography - Wahib, Abdul (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Writing an undergraduate thesis is often a difficult challenge for college students. In this paper, I reflect on my writing experiences in my undergraduate thesis using journal review and stimulated recall to construct my understanding of auto-ethnography in writing an undergraduate thesis. I developed a chronology of the critical occasions during the time I constructed my thesis and reflected upon these events to investigate questions approximately whether my thesis was a piece of auto-ethnography or not. I analyze my experiences using critical incidents to get aha moments. By applying auto-ethnography theories from the experts, I conclude that my paper is a piece of auto-ethnography.